Ontogenesis: a Phenomenon and a Process (on the Problem of the Evolution of Ontogenesis) - Kovtun, M.F. (Вестник зоологии, 2013)
An unconventional approach to the study and analysis of ontogenesis, based on the duality of its nature is proposed: in the first case this is a phenomenon, in second case it is a process. As a phenomenon, ontogenesis covers all manifestations of living, providing the continuity of life on all the levels of its organization, ensures lifespan of a species, regardless of the individual‘s life, and thus the dynamic stability of the cycle of matter and energy flows, the evolution cycles, the biosphere and life in general. As a process it is the implementation of ontogenesis by the way of successive morphogeneses. There is a gap between these components of ontogenesis (the phenomenon and the process) that must be filled out. This is a complex task in the scope of the ontogenesis evolution problem (making the theory of ontogenesis). Предложен нетрадиционный подход к изучению и анализу онтогенеза, исходя из двойственности его природы: с одной стороны, это явление, с другой — процесс. Как явление онтогенез охватывает всю живую природу, обеспечивая непрерывность жизни на всех уровнях её организации; обеспечивает продолжительность жизни вида независимо от жизни индивида и тем самым динамическую стабильность круговорота вещества и потоков энергии, эволюции круговоротов, биосферы и жизни в целом. Процесс — реализация онтогенеза путём последовательных морфогенезов. Между этими составляющими онтогенеза (явление и процесс) — свободное пространство; заполнить его и представляет собой комплекс задач в рамках проблемы эволюции онтогенеза (создание теории онтогенеза).